Printing-Based Assay and Therapy of Antioxidants - Sera Hong (Antioxidants, 2020)
Antioxidants are essential in regulating various physiological functions and oxidative deterioration. Over the past decades, many researchers have paid attention to antioxidants and studied the screening of antioxidants from natural products and their utilization for treatments in diverse pathological conditions. Nowadays, as printing technology progresses, its influence in the field of biomedicine is growing significantly. The printing technology has many advantages. Especially, the capability of designing sophisticated platforms is useful to detect antioxidants in various samples. The high flexibility of 3D printing technology is advantageous to create geometries for customized patient treatment. Recently, there has been increasing use of antioxidant materials for this purpose. This review provides a comprehensive overview of recent advances in printing technology-based assays to detect antioxidants and 3D printing-based antioxidant therapy in the field of tissue engineering. This review is divided into two sections. The first section highlights colorimetric assays using the inkjet-printing methods and electrochemical assays using screen-printing techniques for the determination of antioxidants. Alternative screen-printing techniques, such as xurography, roller-pen writing, stamp contact printing, and laser-scribing, are described. The second section summarizes the recent literature that reports antioxidant-based therapy using 3D printing in skin therapeutics, tissue mimetic 3D cultures, and bone tissue engineering.